(untitled) (Gestão & Regionalidade, 2024)
Objective: The objective of this work is to analyze the main scientific productions on the value codestruction (VCD) and verify its evolution over time, presenting its trends and possible gaps, which can help future research. Methodology: The development of the work was based on a literature review, with the aid of Bibliometrics, with collection in the Web of Science database. Results: They point out that articles about VCD are still incipient. More recent works explore CDV in the shared economy environment, study the effect of showrooming on value destruction and how VCD arises, when analyzed from the perspective of service providers. Practical Implications: The contribution given is a greater understanding of the topic and a direction for new studies that collaborate with researchers and managers to avoid a loss of value during the interaction processes in B2B, B2C or C2C relationships.